Quality improvement intervention to increase colorectal cancer screening at the primary care setting: a cluster-randomised controlled trial - Laura Gutierrez; Ezequiel García Elorrio; Vilma Irazola; Marilina Santero; Juan Ignacio Ruiz; Mario Sánchez; Ignez Tristao; Cintia Spira; Julia Ismael; Ana Soledad Cavallo; Yanina Mazzaresi; Ana Maria Nadal; et al. (BMJ Open Quality)
Background Approximately 81% of deaths in Argentina are from chronic non-communicable diseases and 21% caused by cancer. Colorectal cancer (CRC) is the second most frequent cancer in Argentina. Even though CRC screening has been recommended for adults from 50 to 75 years old by using a faecal immunochemical test (FIT) annually, screening rates remain below 20% in the country.Methods We conducted an 18-month, two-arm, pragmatic cluster-randomised controlled trial evaluating the effect of a quality improvement intervention, based on the Plan-Do-Study-Act cycles, considering barriers and catalysts to articulate theory and practice, to increase CRC screening rates using FITs at primary care level. The study involved ten public primary health centres in Mendoza province, Argentina. The primary outcome measure was the rate of effective CRC screening. Secondary outcomes were the rate of participants with a positive FIT, tests with invalid results and the rate of participants referred for colonoscopy.Results Screening was effective in 75% of the participants in the intervention arm vs 54.2% in the control arm, OR 2.5 (95% CI 1.4 to 4.4, p=0.001). These results remained unchanged after adjusting for individual demographic and socioeconomic characteristics. Regarding secondary outcomes, the overall prevalence of positive tests was 17.7% (21.1% in the control arm and 14.7% in the intervention arm, p=0.3648). The overall proportion of participants with inadequate test results was 5.2% (4.9% in the control arm vs 5.5% in the intervention arm, p=0.8516). All the participants with positive tests were referred for colonoscopy in both groups.Conclusions An intervention based on quality improvement strategies proved to be highly successful in increasing effective CRC screening in Argentina’s primary care setting within the public healthcare system.Trial registration number NCT04293315.